Bridging the Innovation Gap for South African Businesses: Exploring the Influence of Leadership Styles on Innovation Management - Collier, Michael James (University of the Witwatersrand, Johannesburg, 2024)
In South Africa, businesses in the private sector continue to face a persistent and globally perceived innovation gap that undermines competitiveness, adaptability, and at a macro level long-term economic growth and sustainability. Despite growing recognition of innovation as a driver of growth, many South African organisations struggle to integrate effective innovation management into their strategic operations. This study investigates the role of leadership in bridging this innovation gap by exploring how transformational and participative leadership styles influence three key areas of innovation management: innovation adoption, fostering a culture of innovation, and ensuring innovation sustainability. The research follows a qualitative, exploratory design, drawing on semi-structured interviews with senior business leaders operating in innovation-driven industries across South Africa. Participants were purposively selected based on their leadership experience and active involvement in strategic innovation initiatives. The study is centred around Rogers’ Diffusion of Innovations Theory and Schein’s Model of Organisational Culture, which together provide insights and a theoretical framework for understanding some elements of leadership’s impact on organisational innovation practices. Findings reveal that both leadership styles contribute significantly to the speed, effectiveness, and sustainability of innovation efforts. Transformational leaders promote vision-driven adoption and strategic alignment, while participative leaders cultivate inclusive innovation cultures that empower employees and enhance innovation adoption. However, a critical gap exists in formal innovation succession planning across most organisations regardless of leadership style at the helm. The study concludes that leadership is a pivotal lever in embedding innovation into organisational DNA. By aligning leadership development with structured innovation governance and orientated towards transformational and participative leadership practices, South African businesses can enhance their resilience, drive economic transformation, and position themselves more competitively in the global innovation landscape.
A research report submitted in fulfillment of the requirements for the Master of Business Administration, in the Faculty of Commerce Law and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2025
Keywords: UCTD; Innovation Gap; South African Businesses; Leadership Styles; Innovation Management; SDG-9: Industry, innovation and infrastructure; SDG-11: Sustainable cities and communities